Mechanical Properties of Ferrochrome Based Hardfacing Layers Coated on AISI 1020 Steel Obtained by the Aid of Plasma Transfer Arc (PTA) Process - Cay, Vedat Veil; Ozan, Sermin; Topuz, Polat; Kolukisa, Sedat (Carl Hanser Verlag, 2010)
Mechanical properties of ferrochrome based hardfacing layers coated on AISI 1020 steel obtained by the aid of Plasma Transfer Arc (PTA) was experimentally studied. Ferrochrome powders were mixed with sodium silicate gel to avoid spreading. The mixture was laid to 1.5 x 8 x 100 mm slots machined on AISI 1020 steel. Hardfacing layer was performed by PTA process under pure Argon as protective gas with 130 A/20 V power supply. Scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), micro hardness and abrasive tests were employed for the evaluation of ferrochrome alloyed coating. Hardfacing was successfully performed under given conditions. Microstructural changes and formations (phases) significantly improved hardness, abrasive wear resistance and integrity of hardfacing layer.
Mechanische eigenschaften von durch Plasma-pulver-auftragschweißen (PTA) auf AISI 1020-stahl aufgetragenen hartstoffschichten auf ferrochrombasis
Keywords: Microstructure